THE USE OF ANTCONC TO INVESTIGATE THE PATTERN OF CORPUS REPRESENTATION IN JOKO WIDODO’S PRESIDENTIAL SPEECH - Simanjuntak, Faido M. P. (Universitas Methodist Indonesia, 2023)
This research investigates the patterns of representation in Joko Widodo’s corpus of presidential speech. The research method used is a mixed method that combines quantitative and qualitative analysis. The data of the research are transcriptions of President Joko Widodo’s speech text in 2015 and in 2018. In order to be processed with a corpus analysis tool, the data is stored in a text file or .txt format with UTF-8 encoding. The instrument which is used in this study is AntConc. It also brings up words that often appear and keywords in the corpus and analyzes text patterns with certain letter arrangements. Regarding patterns in the text, several appear from words contained in the corpus. Among them are the existence of words that have prefixes, suffixes, prefixes and suffixes, and repetition. Further, from the frequency and keyword analysis, it can be seen that Joko Widodo is focusing his attention on achieving the goals for the Indonesian nation and state, both in the 2015 and 2018 speech texts. It can be concluded, therefore, that Widodo is consistent in his speech patterns. On the other hand, this may be considered a new breakthrough because the speech from 2018 uses the same speech patterns as the speech from three years earlier.